A study on public awareness and acceptance on "No plastic bag" campaign in reducing the usage of plastic bags / Vera Peter Chin - Peter Chin, Vera (2013)
Plastic bag wastes pose serious environmental pollutions and health problems in human and animals. Some estimate that plastic bags are polluting our earth at a speed of 1 million plastic bags per minute, Many countries, including Malaysia, have made their effort on reducing the usage of plastic bags by implementing "No Plastic bag" campaign, some measures work some do not. Among those measures, public awareness of the pollution caused by plastic bags and public acceptance of a world without plastic bag seem to be two important factors for people to reduce their usage of plastic bags. This research is to find out whether public awareness and acceptance do have effect on their motivation to reduce their plastic bags usage. A questionnaire is designed and distributed and data collected to find out the relation among these two factors and the potential effect on the motivation to reduce the usage of plastic bags.